MIXTURE FORMATION ANALYSIS OF POLYOXYMETHYLENETHER INJECTION - Peter, Andreas; Siewert, Bernd; Rieß, Sebastian; Strauß, Lukas; Pastoetter, Christian; Wensing, Michael (Atomization and Sprays, 2020)
Polyoxymethylenether (OME) is a promising fuel for CO2 reduction and a prospective change in the transportation sector. To see the effects of different fuel properties on mass flow rate and mixture formation, OME 3, OME 4, and a mixture of OME 3 and OME 4 (called OME Mix) are compared to European standard diesel fuel. They are investigated for a passenger car and two different commercial vehicle injectors with different nozzle hole diameters at engine relevant conditions of 5 MPa ambient pressure and 873 K ambient temperature. Mass flow rate measurements and optical measurement techniques like Mie scattering and Schlieren imaging are applied feeding the spray model of Musculus and Kattke to investigate the mixture formation. Additionally, a hydraulic and a computational fluid dynamic simulation of the internal nozzle flow are conducted to derive the fuel influence on the needle motion. The results show a strong influence of OME on the mass flow rate development via the correlated needle motion for commercial vehicle nozzle sizes. Depending on the fuel properties, the mass flow rate of OME is retarded in comparison to diesel under equal boundary conditions. The fuel-dependent needle opening impresses different initial momentum fluxes onto the spray. This hydraulic difference cannot be compensated in the upstream flow whereas the stream outside the hole follows the classical momentum conservation. For passenger car nozzle sizes the differences in mass flow rate and needle motion between OME and diesel fuel are not that distinctive, which lead to less deviations of the initially momentum fluxes.
Keywords: polyoxymethylenether (OME); mixture formation